Some General Properties of the Inverse Shadowing Property (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The inverse shadowing property is concentrated, it has important properties and applications in maths. In this paper, some general properties of this concept are proved.  Let  ( be   a metric space: ( → (  be maps have the inverse shadowing property. We show the maps    ∘ ,    have the inverse shadowing property.If and :( , ????) →( ,????) are mapped on a metric space ( ,????) have the inverse shadowing property, We show the maps   +   and   .  have the inverse shadowing property.